2024
DOI: 10.1108/ijhrh-08-2021-0153
|View full text |Cite|
|
Sign up to set email alerts
|

Self-compassion: the influences on the university students’ life satisfaction during the COVID-19 outbreak

Abstract: Purpose This study investigates the relationship between self-compassion and life satisfaction, and there is a significant statistical correlation between some dimensions of the self-compassion scale (family, self-kindness, common human feelings and mental alertness). Design/methodology/approach The researcher used the Self-Compassion scale prepared by Neff (2003) translated by the researchers, in a sample of 150 students in Egypt, and Multidimensional Student’s Life Satisfaction Scale, developed by Huebner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A positive relationship between SC and LS has been observed, with individuals who experience more SC feeling more satisfied with their lives [ 13 ]. This was also supported by a study on students, which showed that positive dimensions of SC (self-kindness, common humanity, mindfulness) were positively related to LS [ 26 ]. Meanwhile, negative dimensions such as self-criticism were negatively related to LS, while there was no statistical significance with the dimensions of isolation and over-identification [ 26 ].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…A positive relationship between SC and LS has been observed, with individuals who experience more SC feeling more satisfied with their lives [ 13 ]. This was also supported by a study on students, which showed that positive dimensions of SC (self-kindness, common humanity, mindfulness) were positively related to LS [ 26 ]. Meanwhile, negative dimensions such as self-criticism were negatively related to LS, while there was no statistical significance with the dimensions of isolation and over-identification [ 26 ].…”
Section: Introductionmentioning
confidence: 53%
“…The relationship between SC, LS and SH among university students during COVID-19 is limited. Studies show a positive relationship between SC and LS, where individuals who experience more SC feel more satisfied with their lives [ 13 , 26 ]. Research on the relationship between SC and SH in university students during COVID-19 is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they argued that these challenges could be overcome through careful planning and execution, as well as ongoing evaluation and refinement [34]. Overall, Roberts et al [13] study highlights the potential of experiential marketing as a powerful tool for building strong customer relationships and driving business growth but also underscores the importance of careful planning, execution, and evaluation; based upon the above literature following hypotheses have been proposed [35]. H1 -Do immersive experiences impact audience perception in Indian performing art educational institutions?…”
Section: Review Of Literaturementioning
confidence: 99%